Preparation of LaNiO3 Perovskite by Oxalate and Carbonate Precursor Method for Utilization as Catalyst for High-temperature Decomposition of N2O - Bělina, Petr; Sádovská, Galina; Krejčíková, Veronika; Dohnalová, Žaneta; Šulcová, Petra (Springer, 2019)
The mixed oxide LaNiO3 with perovskite structure was prepared by two relatively new and unconventional methods including preparation and thermal decomposition of mixed metal oxalate or carbonate precursors. The intermediates were prepared by reaction in a highly concentrated suspension (paste). The thermal decomposition conditions of these intermediates were described, and the final calcination temperatures were determined, which were done using thermal analysis methods and X-ray diffraction. During the decomposition of mixed carbonates, one-phase LaNiO3 is produced directly, and in case of decomposition of oxalates, a mixture of LaNiO3 and La2O3 is produced due to the formation of La2O2CO3 during the heating. Catalytic decomposition of nitrous oxide at high temperature (650-930 °C) and high loading (GHSV = 350,000 h(-1)) has shown high LaNiO3 activity, even at lower temperatures. The results were compared with the same compound obtained by co-precipitation and by solid-state reaction. Methods of preparation based on decomposition of oxalate and carbonate intermediates lead to the preparation of materials with appropriate composition, morphology, specific surface and high catalytic activity.
Příprava perovskitu LaNiO3 pomocí šťavelanových a uhličitanových prekurzorů pro využití jako katalyzátoru při vysokoteplotním rozkladu N2O
Keywords: perovskite; LaNiO3; N2O decomposition; oxalate precursor method; carbonate precursor method; thermal decomposition; mixed metal oxides; perovskit; LaNiO3; rozklad N2O; metoda šťavelanových prekurzorů; metoda uhličitanových prekurzorů; termický rozklad; směsné kovové oxidy